Are there gender differences in left ventricular remodeling after myocardial infarction in rats? - Antonio,Ednei Luiz (2015)
Objective: An unclear issue is whether gender may influence at cardiac remodeling after myocardial infarction (MI). We evaluated left ventricle remodeling in female and male rats post-MI. Methods: Rats were submitted to anterior descending coronary occlusion. Echocardiographic evaluations were performed on the first and sixth week post-occlusion to determine myocardial infarction size and left ventricle systolic function (FAC, fractional area change). Pulsed Doppler was applied to analyze left ventricle diastolic function using the following parameters: E wave, A wave, E/A ratio. Two-way ANOVA was applied for comparisons, complemented by the Bonferroni test. A P≤=0.05 was considered significant. Results: There were no significant differences between genders for morphometric parameters on first (MI [Female (FE): 44.0±5.0 vs. Male (MA): 42.0±3.0%]; diastolic [FE: 0.04±0.003 vs. MA: 0.037±0.005, mm/g] and systolic [FE: 0.03±0.0004 vs. MA: 0.028±0.005, mm/g] diameters of left ventricle) and sixth (MI [FE: 44.0±5.0 vs. MA: 42.0±3.0, %]; diastolic [FE: 0.043±0.01 vs. MA: 0.034±0.005, mm/g] and systolic [FE: 0.035±0.01 vs. MA: 0.027±0.005, mm/g] of LV) week. Similar findings were reported for left ventricle functional parameters on first (FAC [FE: 34.0±6.0 vs. MA: 32.0±4.0, %]; wave E [FE: 70.0±18.0 vs. MA: 73.0±14.0, cm/s]; wave A [FE: 20.0±12.0 vs. MA: 28.0±13.0, cm/s]; E/A [FE: 4.9±3.4 vs. MA: 3.3±1.8]) and sixth (FAC [FE: 29.0±7.0 vs. MA: 31.0±7.0, %]; wave E [FE: 85.0±18.0 vs. MA: 87.0±20.0, cm/s]; wave A [FE: 20.0±11.0 vs. MA: 28.0±17.0, cm/s]; E/A [FE: 6.2±4.0 vs. MA: 4.6±3.4]) week. Conclusion: Gender does not influence left ventricle remodeling post-MI in rats.